Relação entre coping, traços de personalidade e apoio social e suas repercussões em sobreviventes de queimaduras graves - Frota, Priscilla Maria Pires (2010)
Previous studies have demonstrated that both the experience of stressing events and the strategies chosen to deal with them greatly influence people s adaptation and welfare. Taking this into consideration, the main goal of the present study was to examine the existence of correlation among the use of coping strategies, personality, and social support in a group of burn survivors. Initially, a theoretical review on the aforementioned themes was carried out, and, posteriorly, an empirical study was developed. In order to perform the empirical study, the participants answered questions regarding their sociodemographics. For the extraction and evaluation of data such as the coping strategies adopted, social support received and perceived from the social network of each participant, as well as the personality traits, the following instruments were used: Coping Strategy Indicator, Personality Markers, and MOS Social Support Survey. The results obtained evidenced that the sample analyzed presented correlation among the variables coping, personality markers, and social support, demonstrating that socialization correlated positively with reported social support whereas neuroticism correlated negatively with reported social support. It is important to emphasize that, differently from other studies, no significant relationships were found between social support and coping in the sample analyzed. These data are useful to a better planning of the types of intervention that should be implemented in the treatment of burn survivors, based on their peculiarities, so that their results and consequent adaptation to the new routine can be optimized.